Kadar glukosa darah pada wanita menopause: Studi di Puskesmas Muara Dua Kota Lhokseumawe - Wahab, Irwana; Setiyawati, Dewi; Safitri, Yussi Bunga (Poltekkes Kemenkes Aceh, 2025)
Background: Type 2 Diabetes Mellitus (T2DM) is a chronic metabolic disease with increasing prevalence among middle-aged and older women, particularly during menopause, when estrogen decline can trigger insulin resistance and visceral fat accumulation. Local data on blood glucose profiles in postmenopausal women at the primary care level remain limited.Objectives: To describe blood glucose levels among menopausal women attending Puskesmas Muara Dua, Lhokseumawe.Methods: This descriptive quantitative study involved all menopausal women visiting Puskesmas Muara Dua Laboratory between February 6–17, 2023 (n=27, total sampling). Capillary blood glucose was measured using the EasyTouch GCU device via POCT method. Blood glucose levels were classified as normal (<140 mg/dL, postprandial) or abnormal (≥140 mg/dL) following WHO/ADA standards. Data were analyzed descriptively as frequencies and percentages.Results: Of the 27 participants, 59,3% had abnormal blood glucose (≥140 mg/dL). The highest proportion of abnormal values occurred in the 50–59 age group (71,4%; mean 228,0 mg/dL), followed by 60–69 years (55,6%; mean 179,,7 mg/dL), and 70–79 years (25,0%; mean 142,5 mg/dL). Moderate to severe hyperglycemia (201–300+ mg/dL) was observed in 13 respondents (48,1%), indicating substantial risk for diabetic complications.Conclusion: A majority of menopausal women in this study exhibited abnormal blood glucose, with the highest prevalence in the early postmenopausal age group. Regular screening, lifestyle modification counseling, and prompt medical follow-up are crucial to prevent T2DM-related complications in this population.